EFEKTIVITAS LOGISTIK HALAL SELAMA PANDEMI COVID-19 DALAM PROSES DISTRIBUSI PRODUK PANGAN - Wahyudi, Sofyan (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2022)
Halal products are an important need for consumers in Indonesia, due to Indonesia being the most populous Muslim-majority country, halal assurance is not only considered from raw materials and production processes but also logistics processes when distributing goods from producers to consumers. The government encourages food product producers in Indonesia to maintain the availability of food products, especially during the COVID-19 pandemic, because food is a basic need that is still sought after in difficult times. Evaluation of the halal logistics process in the food product distribution process needs to be done by calculating the efficiency value in order to support companies to maintain consumer confidence in halal product guarantees. This paper aims to study the performance of halal logistics in the distribution process of products to consumers located in various cities in Indonesia during the covid-19 pandemic. The case study will be conducted at PT. ABC is a food manufacturer located in Bekasi, West Java. This study will use the Data Envelopment Analysis (DEA) method to calculate the efficiency value of each distribution process in various destination cities, DEA is a nonparametric method in operations and economics research to measure the efficiency value. The results of this study indicate that the logistics halal distribution process to the cities of Semarang, Manado, and Medan is in the efficient category, therefore the distribution system pattern can be maintained, while the distribution process to the cities of Denpasar and Makassar is considered inefficient, so it is necessary to evaluate and improve to maintain the halal principle. in the distribution of goods.